Pengaruh Lingkungan Kerja, Profesionalisme dan Kepuasan Kerja Terhadap Komitmen Kerja Pada Unit Penyelenggara Bandar Udara (UPBU) Kelas I Mopah Merauke - Indra Gautama; Suratini Suratini; Mery Noviyanti (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
In theory, work commitment can be influenced by various factors, including the work environment, professionalism, and job satisfaction. Research on work commitment in the airport sector managed by the government is still very rare, therefore the purpose of this study is to determine the effect of the work environment, professionalism, and job satisfaction on employee work commitment at the Class I Mopah Merauke Airport Operations Unit (UPBU). with a population of 110. The sample determination method uses a saturated sample, so that all employees at the UPBU Class I Mopah Office are used as samples. Variable measurements were carried out using a Likert scale. Data analysis was performed using multiple linear regression methods and with SPSS software. The results of the analysis show that the work environment, work professionalism, and job satisfaction have a significant positive effect on employee work commitment in Class I UPBU Mopah Merauke Office. The better the work environment, work professionalism, and job satisfaction, it will lead to better work commitment.